Introduction to infectology. Infections diseases with fecai-oral transmission - Ryabokon, E. V.; Onischenko, T. E.; Furyk, E. A.; Mashko, O. P. (Zaporozhye state medical university, 2014)
Manual for practical training and independent work of students for the 5th year of the Medical Faculty on Infectious Diseases to the Infections diseases with fecal-oral transmission. In manual aid theoretical bases of infectious diseases are expounded with the fecal-oral mechanism of transmission. The questions of etiology, epidemiology, classification of pathogenetic mechanisms, clinics, diagnostics, differential diagnostics, treatment and prophylaxis of intestinal diseases are presented in every part of manuals. In every division theoretical part is presented by charts, algorithms, tables. A manual contains methodical recommendations for independent preparation of students to practical employments, control questions, situational tasks and tests with the standards of answers to every theme of practical lessons. This manual was written for the medical student and presumes a basic knowledge of biology, biochemistry, immunology, therapy, surgery.